Quantitative growth analysis of four corn varieties grown in three plant densities, with the use of fitted mathematical functions - Machado, Eduardo Caruso; Pereira, Antonio Roberto; Fahl, Joel Irineu; Arruda, Hermano Vaz; Silva, William José da; Teixeira, J.P.F. (Pesquisa Agropecuaria Brasileira, 2014)
Four corn varieties were grown in three PD. Within each PD the above varieties did not show any significant difference regarding the biometric characteristics of growth. There was, however, effect duo to the PD. Increase in PD decreased the DW and LA/P without any change in the relative distribution of DM among the plant components. The time variation of DW and LA were conveniently described by the logistic function and the power parabola, respectively. The physiological indices were obtained by handling the above functions and in general presented the following tendencies: a. there was no significant effect of PD on the RGR and LAR; b. CGR and GGR increased with increase in PD; c. apparently the NAR was a function of the demand of carbohydrates by the reproductive organs; d. HI remained constant and about 0,4 for the three densities used; e. at maturation, the SSC was independent of PD and relatively high indicating that the above varieties did not achieve their potential grain production since the carbohydrates left in the stalk represent energy fixed by photosynthesis and unused for grain production; f. husks and cobs were approximately 25-30% of the ear dry weight.